A practical approach to assess leg muscle oxygenation during ramp-incremental cycle ergometry in heart failure - Barroco, Adriano Candido [UNIFESP] (2017)
Heart failure is characterized by the inability of the cardiovascular system to maintain oxygen (O2) delivery (i.e., muscle blood flow in non-hypoxemic patients) to meet O2 demands. The resulting increase in fractional O2 extraction can be non-invasively tracked by deoxygenated hemoglobin concentration (deoxi-Hb) as measured by near-infrared spectroscopy (NIRS). We aimed to establish a simplified approach to extract deoxi-Hb-based indices of impaired muscle O2 delivery during rapidly-incrementing exercise in heart failure. We continuously probed the right vastus lateralis muscle with continuous-wave NIRS during a rampincremental cardiopulmonary exercise test in 10 patients (left ventricular ejection fraction o35%) and 10 age-matched healthy males. Deoxi-Hb is reported as % of total response (onset to peak exercise) in relation to work rate. Patients showed lower maximum exercise capacity and O2 uptake-work rate than controls (Po0.05). The deoxi-Hb response profile as a function of work rate was S-shaped in all subjects, i.e., it presented three distinct phases. Increased muscle deoxygenation in patients compared to controls was demonstrated by: i) a steeper mid-exercise deoxi-Hb-work rate slope (2.2±1.3 vs 1.0±0.3% peak/W, respectively; Po0.05), and ii) late-exercise increase in deoxi-Hb, which contrasted with stable or decreasing deoxi-Hb in all controls. Steeper deoxi-Hb-work rate slope was associated with lower peak work rate in patients (r=–0.73; P=0.01). This simplified approach to deoxi-Hb interpretation might prove useful in clinical settings to quantify impairments in O2 delivery by NIRS during ramp-incremental exercise in individual heart failure patients.